REVOLUTIONIZING LEARNING: THE ROLE OF TECHNOLOGY IN MODERN EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Annotation. Technology has significantly transformed the education sector, enhancing accessibility, engagement, and personalized learning experiences. This paper examines the impact of technology on modern education, exploring innovative tools, methodologies, and their effectiveness. Key aspects such as e-learning platforms, artificial intelligence, and virtual reality in education are analyzed. The study also presents empirical data demonstrating the effectiveness of technology in improving student outcomes.